Elucidating the involvement of apoptosis in postmortem proteolysis in porcine muscles from two production cycles using metabolomics approach - Danyi Ma (Nature Portfolio, 2021)
Abstract Apoptosis has been suggested as the first step in the process of conversion of muscle into meat. While a potential role of apoptosis in postmortem proteolysis has been proposed, the underlying mechanisms by which metabolome changes in muscles would influence apoptotic and proteolytic process, leading to meat quality variation, has not been determined. Here, apoptotic and proteolytic attributes and metabolomics profiling of longissimus dorsi (LD) and psoas major (PM) muscles in pigs from two different production cycles (July–Jan vs. Apr–Sep) were evaluated. PM showed higher mitochondrial membrane permeability (MMP), concurrent with less extent of calpain-1 autolysis and troponin T degradation and higher abundance of HSP27 and αβ-crystallin compared to LD (P < 0.05). Apr–Sep muscles showed concurrence of extended apoptosis (indicated by higher MMP), calpain-1 autolysis and troponin T degradation, regardless of muscle effects (P < 0.05). Metabolomics profiling showed Apr–Sep muscles to increase in oxidative stress-related macronutrients, including 6-carbon sugars, some branched-chain AA, and free fatty acids. Antioxidant AA (His and Asp) and ascorbic acid were higher in July–Jan (P < 0.05). The results of the present study suggest that early postmortem apoptosis might be positively associated with pro-oxidant macronutrients and negatively associated with antioxidant metabolites, consequently affecting meat quality attributes in a muscle-specific manner.